2002
DOI: 10.1080/mmy.40.2.111.114
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of interferon -γ- producing cells in granuloma formation of sporotrichosis

Abstract: Granuloma formation is a common response in the skin infection of sporotrichosis. The involvement of interferon-gamma (IFN-gamma) and inducible nitric oxide synthase (iNOS) in the granuloma formation of sporotrichosis is less known. The aim of this study was to describe by immunohistochemistry the exact tissue distribution of IFN-gamma-positive cells and iNOS-positive cells in the granuloma of skin lesions from patients with sporotrichosis. Formalin-fixed paraffin-embedded skin biopsy sections from five patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Over time, the response changed, and IL-10 production decreased, while the levels of IFN-g increased. In the human disease, IFN-gpositive cells were observed in the upper dermis in lesions in situ [28]. Interestingly, in our study, the levels of IL-10 were notably high during the early phase of the infection when the fungus was present in the viscera, including the spleen.…”
Section: Organmentioning
confidence: 85%
“…Over time, the response changed, and IL-10 production decreased, while the levels of IFN-g increased. In the human disease, IFN-gpositive cells were observed in the upper dermis in lesions in situ [28]. Interestingly, in our study, the levels of IL-10 were notably high during the early phase of the infection when the fungus was present in the viscera, including the spleen.…”
Section: Organmentioning
confidence: 85%
“…When the numbers of CD4 + and CD8 + cells increase and IFN-g production is enhanced in ACD, the condition is considered to be CHS [40,41]. Inflammation caused by Trichophyton infection was previously considered to be Th1-dominant CHS because IFN-g production increases in skin tissue and PBMC in inflammatory regions with flare and swelling [8,9]. However, the Th2-dominant condition with enhanced IL-4, IL-5, and blood IgE productions in patients with atopic dermatitis and immunodeficiency has recently been reported [11][12][13], showing differences in Trichophyton-induced inflammatory reactions due to the Th1/Th2 balance in infected patients.…”
Section: Discussionmentioning
confidence: 98%
“…The other is the innate immune system, which recognizes components common in pathogens and operates defense mechanisms [5,6] According to existing immunological knowledge concerning Trichophyton-induced inflammation, peripheral blood mononuclear cells (PBMC) show potent proliferative ability in response to Trichophyton antigen and IFN-g is produced in patients with Trichophyton infection [7]. In the lesions, IFN-g gene expression was found to be enhanced and IFN-g-positive CD4 + cells were present [8,9], suggesting that Trichophyton-induced superficial skin mycosis is Th1-type contact hypersensitivity (CHS) [10]. However, in some recently reported studies, patients with atopic dermatitis and immunodeficiency showed Th2-dominant reactions producing IL-4, IL-5, and IgE at high levels upon infection with Trichophyton [11][12][13], and different responses of the acquired immune system among patients have been identified.…”
Section: Introductionmentioning
confidence: 97%
“…26 CD68 + histiocytes have been shown to contain various factors including tumor necrosis factor (TNF)-alpha, interferon gamma, and matrix metalloproteinases in granulomatous inflammations of various tissues, including the skin. [27][28][29][30][31] The antigen for HAM56 that reacts with human macrophages is so far uncharacterized. It also reacts with human tissue macrophages.…”
Section: Discussionmentioning
confidence: 99%